The legacy of polio: 2 cases of post-polio syndrome and review - Katherine A. Mafla-Ayub (Revista Mexicana de Neurociencia, 2022)
Post-polio syndrome (PPS) is a rare neurological disorder that affects 20-40% of paralytic and non-paralytic polio survivors. It is estimated that about 15 million people worldwide are survivors of the polio infection that occurred during the 1940s and 1950s, until the vaccine was first introduced. Its main characteristic is the appearance of de novo muscle weakness or its increase and atrophy, accompanied by other symptoms such as fatigue, joint, bone or muscle pain, intolerance to cold, and bulbar symptoms (involvement of swallowing, speech and breathing). PPS usually affects performance in daily activities with a negative effect on patients’ quality of life. We present two cases with a diagnosis of PPS, with a current review of the literature.